Genetic and Genomic Tools to Asssist Sugar Beet Improvement: The Value of the Crop Wild Relatives - Monteiro, Filipa; Frese, Lothar; Castro, Sílvia; Duarte, Maria C.; Paulo, Octávio S.; Loureiro, João; Romeiras, Maria M. (Frontiers in Plant Science, 2018)
Sugar beet (Beta vulgaris L. ssp. vulgaris) is one of the most important European crops for both food and sugar production. Crop improvement has been developed to enhance productivity, sugar content or other breeder’s desirable traits. The introgression of traits from Crop Wild Relatives (CWR) has been done essentially for lessening biotic stresses constraints, namely using Beta and Patellifolia species which exhibit disease resistance characteristics. Several studies have addressed crop-to-wild gene flow, yet, for breeding programs genetic variability associated with agronomically important traits remains unexplored regarding abiotic factors. To accomplish such association from phenotype-to-genotype, screening for wild relatives occurring in habitats where selective pressures are in play (i.e., populations in salt marshes for salinity tolerance; populations subjected to pathogen attacks and likely evolved resistance to pathogens) are the most appropriate streamline to identify causal genetic information. Ultimately, the selection of sugar beet CWR species based on genomic tools, rather than selecting random variants with desirable characteristics is a promising, but still seldom explored route towards the development of improved crops. In this perspective, a viable streamline for sugar beet improvement is proposed through the use of different genomic tools by recurring to sugar beet CWRs and focusing on agronomic traits associated with abiotic stress tolerance. Overall, identification of genomic and epigenomic landscapes associated to adaptive ecotypes, along with the cytogenetic and habitat characterization of sugar beet CWR, will enable to identify potential hotspots for agrobiodiversity of sugar beet crop improvement towards abiotic stress tolerance.